Haemophilia B Curative FIX Production from a Low Dose UCOE-based Lentiviral Vector Following Hepatic Pre-natal Delivery - Yu-cheng Kao, Vincent; Ferreira, Sonia; N. Waddington, Simon; N. Antoniou, Michael (Current Gene Therapy, 2016)
The ubiquitous chromatin opening element from the human HNRPA2B1-CBX3 housekeeping gene locus (A2UCOE) is able to provide stable and cell-to-cell reproducible levels of transgene expression regardless of target cell genome integration site with efficacy demonstrated in adult, embryonic and induced pluripotent stem cells and their differentiated progeny in vitro and in vivo. Here we evaluate the ability of A2UCOE-based lentiviral vectors to confer stable expression following pre-natal delivery in mice. Our results show stable post-natal A2UCOE-eGFP and A2UCOE-luciferase lentiviral vector presence in both the liver and haematopoietic system with concomitant persistence of expression demonstrating efficient transduction of both fetal liver and haematopoietic stem cells. In addition, we find that an A2UCOE-FIX lentiviral vector produces comparable amounts of plasma FIX protein to that obtained from a SFFV-FIX construct. Furthermore, the A2UCOE-FIX vector shows that at a low (0.19) average vector copy number per liver cell, it can provide stable levels of plasma FIX production, which would convert severe haemophilia B (<1%) to a mild phenotype (≈20%). Our results provide proof-ofprinciple for low dose pre-natal A2UCOE-based LV delivery to the liver as a therapeutic option for haemophilia B and potentially other metabolic conditions.
Keywords: Pre-natal